Design and performance analysis of pattern reconfigurable MIMO antennas for mobile smartphones. Issue 1 (January 2017) - Shoaib, Sultan; Shoaib, Nosherwan; Shoaib, Imran; Chen, Xiaodong
ABSTRACT: This paper presents compact pattern reconfigurable antennas for mobile handsets in MIMO configuration. Each antenna of the MIMO configuration being coupled fed monopole in meandered form is capable of covering several cellular frequency bands in the range of 1.75–2.67 GHz including 4G‐LTE, 2G‐GSM, 3G‐UMTS, and WLAN. The MIMO antennas are printed diagonally at the left and right no‐ground portions on the top layer of the substrate to enhance the isolation performance. The substrate used is FR‐4 with relative permittivity of 4.35 and loss tangent of 0.02. The volume of the substrate is 120 × 65 × 1.6 mm 3 with each antenna occupying an area of 26.5 × 14.5 mm 2 . The pattern reconfigurability is achieved by connecting and disconnecting a 4.5 × 2 mm 2 metallic strip using the p‐i‐n diode switch. The antennas are pattern reconfigurable in the frequency range of 1.9–2.1 GHz. The isolation achieved is better than 16 dB over all the frequency bands covered by each antenna. A prototype has been fabricated and tested. The simulated and measured results show a good performance of the MIMO antennas. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:148–156, 2017